Constructing seasonal records of Ross Ice Shelf elevation changes using ICESat altimetry data - Lexian Yuan; Shengkai Zhang; Feng Xiao; Xiao Li; Tingguo Lu; Hui Luo; Fei Li (Geodesy and Geodynamics)
Ice shelves are important passageways for ice sheets flowing into the ocean. Through iceberg calving and basal melting, ice shelves exert considerable influence on the mass balance of the Antarctic Ice Sheet and glacier stability. The Ross Ice Shelf (RIS), the largest body of floating ice on Earth, plays an essential role in any changes in the mass balance of the Antarctic Ice Sheet. The long-term elevation change trend of RIS has been calculated with multiple satellite altimetry in previous studies. However, the seasonal variations were less revealed. Based on crossover analysis and indirect observation adjustments, this study proposed a new method for constructing seasonal records for surface elevation changes in the RIS using ICESat laser altimetry data from 2003 to 2009. The results showed that surface elevation changes exhibited seasonal variations with fluctuations over 20 cm, and the seasonal change characteristics were closely related to the temperature. Interannual variations in RIS surface elevation decreased from 2003 to 2009 at a rate of 2 cm/yr. From March 2003 to April 2007, the surface elevation decreased at 3.7 cm/yr; however, after April 2007, the surface elevation increased at 5.5 cm/yr. The more recent stages of surface elevation growth have been influenced by reductions in the summer basal melt, which is related to the decreases in ocean heat content.